2023
DOI: 10.1039/d3ob00171g
|View full text |Cite
|
Sign up to set email alerts
|

An attempt to consider cooperativity in helical-sense preferences induced in fused macrocycles

Abstract: We synthesized bis and tris(macrocycle)s in which a two- or threefold macrocycle was fused and each adopted twisted forms with M- or P-helicity. According to the sense of twisting in...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 27 publications
(29 reference statements)
0
0
0
Order By: Relevance
“…If only a single pair of diastereomeric (pseudo-enantiomeric) conformers with M - or P -helicity could be present in the solution ( Scheme 1b , controlled), that would be suitable for estimating the population as a diastereomeric ratio ( M N / P N ), as with a monomeric case ( N = 1). This was the case for 2, 10 4, 11 5, 10, 12 and 11. 12 Fortunately, the diastereomeric ratio was quantitatively estimated for 2, 4, and 5.…”
Section: Introductionmentioning
confidence: 68%
See 3 more Smart Citations
“…If only a single pair of diastereomeric (pseudo-enantiomeric) conformers with M - or P -helicity could be present in the solution ( Scheme 1b , controlled), that would be suitable for estimating the population as a diastereomeric ratio ( M N / P N ), as with a monomeric case ( N = 1). This was the case for 2, 10 4, 11 5, 10, 12 and 11. 12 Fortunately, the diastereomeric ratio was quantitatively estimated for 2, 4, and 5.…”
Section: Introductionmentioning
confidence: 68%
“…S14†), we reported that the diastereomeric ratio (α/β) induced at 223 K in chloroform was estimated to be 2.3 for M - 1 and P - 1 , 4.7 for MM - 2 and PP - 2 , and 9.9 for MMM - 4 and PPP - 4 by linear extrapolation. 11 In a similar manner, the value of α/β was estimated to be ca. 51 for MMMM - 5 and PPPP - 5 (Fig.…”
Section: Resultsmentioning
confidence: 91%
See 2 more Smart Citations